2014
DOI: 10.1186/1471-2202-15-36
|View full text |Cite
|
Sign up to set email alerts
|

A two years longitudinal study of a transgenic Huntington disease monkey

Abstract: BackgroundA two-year longitudinal study composed of morphometric MRI measures and cognitive behavioral evaluation was performed on a transgenic Huntington’s disease (HD) monkey. rHD1, a transgenic HD monkey expressing exon 1 of the human gene encoding huntingtin (HTT) with 29 CAG repeats regulated by a human polyubiquitin C promoter was used together with four age-matched wild-type control monkeys. This is the first study on a primate model of human HD based on longitudinal clinical measurements.ResultsChanges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 61 publications
(91 reference statements)
3
69
0
Order By: Relevance
“…Together these results demonstrate that HD rhesus monkeys exhibit some of the key behavioral and immune features found in HD patients. Therefore, these results, along with previous findings in these same animals, suggest that the HD monkey model embodies a full array of HD symptoms (Chan et al, 2014, 2015), making it ideal for narrowing down preclinical pharmacological targets and identifying promising new treatments for HD patients.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Together these results demonstrate that HD rhesus monkeys exhibit some of the key behavioral and immune features found in HD patients. Therefore, these results, along with previous findings in these same animals, suggest that the HD monkey model embodies a full array of HD symptoms (Chan et al, 2014, 2015), making it ideal for narrowing down preclinical pharmacological targets and identifying promising new treatments for HD patients.…”
Section: Discussionsupporting
confidence: 62%
“…Considering these similarities between human and nonhuman primates, the transgenic HD rhesus monkey (HD monkey) model holds great promise for future HD treatment development because nonhuman primates may be able to model the full spectrum of HD patient symptoms. Recently we have shown that HD monkeys exhibit subtle cognitive deficits (Chan et al, 2014, 2015), difficulty with fine motor tasks (Chan et al, 2015), as well as volume reduction and nuclear inclusions of mutant HTT aggregates in brain areas to similar human HD patients (Chan et al, 2015). However, little is known about whether HD monkeys exhibit these pre-manifest/early HD symptoms of emotional dysregulation and innate immune hyperactivity.…”
mentioning
confidence: 99%
“…Although these transgenic monkeys showed some polyQ-disease–like features, including intranuclear inclusions in the brain, their symptoms appeared immediately after birth, and unfortunately, the symptomatic animals died without germline transmission of the transgenes. In a more recent study, the same group has succeeded in producing transgenic HD rhesus monkey models exhibiting slower onset and progression with the onset of behavioral phenotypes at 8 or 16 months of age (Chan et al 2014, 2015). Furthermore, they have confirmed germline transmission of the transgene in the second-generation offspring generated from one of the founder monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, stereotaxic surgery has been used to target the naïve NHP putamen to assess the safety of partially reducing HTT expression via 1) AAVs expressing microRNA constructs (12, 13) or siRNAs delivered through a cannula placed into the putamen (14). With the recent creation of a transgenic HD monkey bearing a fragment of human mutant HTT (15), it is anticipated that stereotaxic surgery will be used to evaluate a variety of therapeutics in this NHP model in the near future.…”
Section: Introductionmentioning
confidence: 99%